Microstructure, hardness and mechanical properties of two different unalloyed tantalum wires deposited via wire + arc additive manufacture. (September 2019) - Marinelli, G.; Martina, F.; Ganguly, S.; Williams, S.
Abstract: An innovative way of producing large-scale unalloyed tantalum parts, based on the Wire + Arc Additive Manufacturing process, has been developed in this study. Two different unalloyed tantalum wires have been used to deposit 200-mm-long structures in tantalum. The effect of the wire chemistry on microstructure, hardness, porosity, mechanical properties and strain localisation has been investigated. The deposits showed high integrity and excellent mechanical properties, with yield strength, ultimate tensile strength and elongation as high as 234 MPa, 261 MPa, and 36%, respectively. Indeed, yield strength was higher than commercially available tantalum, even though, in this study, the grains were large and had a high aspect ratio. Wire + Arc Additive Manufacture has clearly shown the potential to produce tantalum components with relatively low cost and reduced lead time, thus offering a new robust and viable manufacturing route. Highlights: Wire + Arc Additive Manufacture is a suitable technique for the production of unalloyed tantalum components The chemistry of the tantalum feedstock has a marked effect on porosity, hardness and mechanical properties The microstructure was characterised by macroscopic bands, caused by the removal of dispersed fine oxide particles The tensile properties of the deposited walls were comparable to those of the substrate material, unlike the total elongation Thermal straining and repetitive thermal cycles had a visible effect on hardness and tensile properties